The impact of physical, nutritional, and mental preparation on triathlon performance - Houston, M.; Dolan, S.; Martin, S. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: There are numerous variables that can impact a triathletes` performance. Research with this population has primarily focused on physical training habits to determine performance predictors, thus the purpose of this study was to explore the impact of nutritional and mental preparation strategies in addition to physical training on race times of Olympic-distance triathletes. METHODS: Triathletes were asked to complete an online survey that focused on physical conditioning, nutritional habits, mental training, and educational experience related to triathlon training. Participants included 272 age-group triathletes (146 males, 126 females). ANOVAs and MANOVAs were conducted to identify variables that significantly related to race time, while a logistic regression was used to determine variables that predicted performance. RESULTS: Race time was predicted by competitive motivation to participate, participation in strength training, and use of intervals during run and swim training. Mental strategies that predicted faster race times included pre-competition routines, use of energizing strategies before a race, and setting outcome goals for races. Nutritional habits did not have an impact on race time. CONCLUSION: The results support the need to go beyond investigating physical training preparation.